(untitled) (Journal of the College of Basic Education, 2022)
Pedagogy means the methods, principles and methods of education, and the set of works that the teacher uses in the context of his job to transfer knowledge and education to his students within a school context. (Hill et al, 2008.23) As for pedagogical content knowledge (P.C.K), it is a mixture of both content and pedagogical knowledge, which corresponds to the subjective experience of the teacher to be able to expand his understanding about how to teach a specific subject by adapting to the needs and abilities of learners, and it is represented in the teaching strategies and methods used in teaching specific curricular content within an educational context Specific directed to achieve specific educational goals and values. (Shulman, 1986: 15) Mathematical literacy refers to the necessary amount of mathematical knowledge of concepts, principles, skills and processes related to mathematics, and the ability to use mathematical thinking methods to solve problems, in addition to knowledge of the historical development of mathematics and the contributions of Arab and Muslim scholars in this development. (Badr, 2010: 204) The current research aims to determine the pedagogical content knowledge (P.C.K) of mathematics instructors in the second intermediate grade To accomplish this aim, the following null hypotheses were formulated: There is no statistically significant difference at the level (0.05) between the mean scores of mathematics teachers and the hypothetical mean to test their mathematical knowledge. There is no statistically significant difference at the level (0.05) between the mean scores of mathematics teachers and the hypothetical mean of their general pedagogical knowledge scale. There is no statistically significant difference at the level (0.05) between the mean scores of mathematics teachers and the hypothetical average for each dimension of pedagogical knowledge of the content (P.C.K) they have. The researcher adopted the descriptive approach, and the research sample was chosen randomly from the research community, which consisted of (74) teachers and mathematics schools for the second intermediate grade, and to achieve the goal of the research the following tools were prepared: A test knowledge of the mathematical content of the second intermediate grade mathematics teachers, which consists of (22) paragraphs of the multiple-choice type with four alternatives. A scale of general pedagogical knowledge for mathematics teachers of the second intermediate grade, which consists of (57) paragraphs. Using the following statistical methods: (t-test for one sample, and Pearson correlation coefficient), the results of the current research showed the following: The middle school mathematics teachers possess a good level of pedagogical knowledge (P.C.K). In light of the research results, the researcher made some recommendations, including: Organizing in-service training courses for mathematics teachers, which may help them, improve their pedagogical content knowledge (P.C.K). As put forward some suggestions, including: Studying the effect of a proposed program in improving the dimensions of pedagogical knowledge of content (P.C.K) among students-teachers in the faculties of education and basic education.